On the transformation of “zincone”-like into porous ZnO thin films from sub-saturated plasma enhanced atomic layer deposition - Perrotta, Alberto; Pilz, Julian; Pachmajer, Stefan; Milella, Antonella; Coclite, Anna Maria (Beilstein Journal of Nanotechnology, 2019)
The synthesis of nanoporous ZnO thin films is achieved through annealing of zinc-alkoxide (“zincone”-like) layers obtained by plasma-enhanced atomic layer deposition (PE-ALD). The zincone-like layers are deposited through sub-saturated PE-ALD adopting diethylzinc and O2 plasma with doses below self-limiting values. Nanoporous ZnO thin films were subsequently obtained by calcination of the zincone-like layers between 100–600 °C. Spectroscopic ellipsometry (SE) and X-ray diffraction (XRD) were adopted in situ during calcination to investigate the removal of carbon impurities, development of controlled porosity, and formation and growth of ZnO crystallites. The layers developed controlled nanoporosity in the range of 1–5%, with pore sizes between 0.27 and 2.00 nm as measured with ellipsometric porosimetry (EP), as a function of the plasma dose and post-annealing temperature. Moreover, the crystallinity and crystallite orientation could be tuned, ranging from a powder-like to a (100) preferential growth in the out-of-plane direction, as measured by synchrotron-radiation grazing incidence XRD. Calcination temperature ranges were identified in which pore formation and subsequent crystal growth occurred, giving insights in the manufacturing of nanoporous ZnO from Zn-based hybrid materials.
Keywords: calcination; PE-ALD; porosity; thin films; ZnO